Implementation Corporate Social Responsibility Of Regional Owned Business Agencies To Help Handling Covid-19 In Kendal - Kuswandriyo, Andhang (VJJ, 2021)
Improve the welfare of the community in the area around the company and corporate responsibility. This can happen because the community feels affected by the environment that comes from the company's operations. The improvement of conditions in the social environment is one way of fulfilling the responsibilities known as corporate social responsibility or CSR. The definition of economic democracy in the national economy is based on the principles of unity, equity, sustainability of function, environmental mobilization, independence, and in maintaining the balance of development and national economic unity, it is important to support the 'main economic institutions; to determine the welfare of the people. CSR activities for the community are a process of migration and are related to the existing resources in the community. Currently, Social Welfare is no longer voluntary in nature but it has become the responsibility of many companies to implement it, although so far there have been no serious sanctions imposed on non CSR companies.